Modeling of a neutron irradiator using Monte Carlo. (November 2020) - Santos, Raphael F.G.; Rebello, Wilson F.; Estrada, Julio J.S.; Medeiros, Marcos P.C.; Silva, Ademir X.; Souza, Edmilson M.; Costa, Rogério F.; Barbosa, Caroline M.; Braga, Kelmo L.; Braz, Delson
Abstract: The Nuclear Engineering Department of the Military Institute of Engineering (SE/7-IME) is designing and simulation a neutron irradiator with 1 Ci of 241 Am- 9 Be source. The objective of this irradiator is to generate a flux of neutrons to be used in research and teaching maintaining, for purposes of radiological protection, the rate of ambient dose equivalent, H*(10), below 10 μSv/h at 30 cm from the surface. This paper presents the proposed irradiator, values of H*(10) at different distances from the irradiator and the neutron flux in different points of the beam irradiation, all calculated using the MCNPX code. Highlights: Modeled cilindrical irradiator using the MCNPX code. Developing a neutron irradiator with 1 Ci of 241 Am- 9 Be source. The rate of ambient dose equivalent, H*(10), below 10 μSv/h at 30 cm from the surface. The shielding allowed the H*(10) rate to be below 10 μSv/h at 30 cm from the surface. The neutron flux decreasing its intensity as a function of distance.